Bronquiolitis en paciente masculino de 4 años. - Cadena Sánchez, Octavio Alexander (2021)
The present clinical case study is based on the care of a 4-year-old patient with bronchiolitis, which was treated in time with the proper procedures to be performed. Inflammation of the bronchioles is defined as a pathology called bronchiolitis, it directly affects pediatric patients, it is classified as one of the most frequent emergencies in this type of patient, it appears in the rainy and humid months, etiologically speaking it is caused by respiratory syncytial virus. Patients with basic pulmonary pathologies are more likely to acquire this type of disease that inflames the bronchioles, in addition to immunocompromised patients such as leukemia, patients who have undergone surgery and bone marrow transplantation. The pathology was assessed using the Wood-Downes scale which immediately helped to clarify the severity of the patient's situation in their health condition, yielding a score of 8, demonstrating severe bronchiolitis, an effective treatment was used to To treat the severity of bronchiolitis, low-flow oxygen therapy was used by nasal cannula at 4 bpm, in addition, nebulization was applied to administer inhaled drugs such as bronchodilators in corresponding doses under the prescription of the treating physician.